2006
DOI: 10.1111/j.1463-1318.2006.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

A paradox explained? Patients with delayed diagnosis of symptomatic colorectal cancer have good prognosis

Abstract: In the context of modern rapid access clinics, symptomatic CRC patients with delay between referral and diagnosis (even if this is several months or occasionally more than a year) have less aggressive tumours and markedly better long-term cure rate than their earlier diagnosed counterparts. Attempts to speed up further the diagnosis would be a waste of time and resources, being unlikely to make an appreciable difference to the overall cure rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
47
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 14 publications
5
47
1
Order By: Relevance
“…The staging of the tumours and the proportions with left-or right-sided tumours or with emergency admissions are also similar. The finding of no relationship between the duration of symptoms and staging or mortality -even with our robust methods of identifying the duration -matches previous reports (Stubbs and Long, 1986;Barillari et al, 1989;Kyle et al, 1991;Mulcahy and O'Donoghue, 1997;Majumdar et al, 1999;Roncoroni et al, 1999;Kiran and Glass, 2002;Gonzalez-Hermoso et al, 2004;Olsson et al, 2004;Bharucha et al, 2005;Khattak et al, 2006;Rupassara et al, 2006). It is likely that two effects are cancelling each other out: inherent biological features of the tumour and ease of diagnosis.…”
Section: Comparison Of Findings With Previous Literaturesupporting
confidence: 86%
See 3 more Smart Citations
“…The staging of the tumours and the proportions with left-or right-sided tumours or with emergency admissions are also similar. The finding of no relationship between the duration of symptoms and staging or mortality -even with our robust methods of identifying the duration -matches previous reports (Stubbs and Long, 1986;Barillari et al, 1989;Kyle et al, 1991;Mulcahy and O'Donoghue, 1997;Majumdar et al, 1999;Roncoroni et al, 1999;Kiran and Glass, 2002;Gonzalez-Hermoso et al, 2004;Olsson et al, 2004;Bharucha et al, 2005;Khattak et al, 2006;Rupassara et al, 2006). It is likely that two effects are cancelling each other out: inherent biological features of the tumour and ease of diagnosis.…”
Section: Comparison Of Findings With Previous Literaturesupporting
confidence: 86%
“…There is a clear relationship between the staging of the cancer and mortality (Mulcahy and O'Donoghue, 1997;Roncoroni et al, 1999;Ponz de Leon et al, 2000;Gonzalez-Hermoso et al, 2004;Olsson et al, 2004). Conversely, most studies have shown no relationship between the duration of symptoms and staging or mortality (Stubbs and Long, 1986;Barillari et al, 1989;Kyle et al, 1991;Mulcahy and O'Donoghue, 1997;Majumdar et al, 1999;Roncoroni et al, 1999;Kiran and Glass, 2002;Gonzalez-Hermoso et al, 2004;Olsson et al, 2004;Bharucha et al, 2005;Khattak et al, 2006;Rupassara et al, 2006). Some have reported an inverse relationship, with a shorter duration of symptoms being associated with both worse staging and worse prognosis (Mulcahy and O'Donoghue, 1997;Olsson et al, 2004;Rupassara et al, 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10] For the rest of this review, I concentrate upon activity between B and D, so from first presentation to referral for definitive investigation and take most of my examples from the four commonest cancers, breast, prostate, lung, and colorectal.…”
Section: Introductionmentioning
confidence: 99%